Recognition Of Historical Building Using Augmented Reality Application Using Feature From Accelerated Segment Test (Fast) Algorithm - Ihsan, Ahmad; Fadillah, Nurul; Susanti, Rita; Abdullahr, T. Rafli (Politeknik Negeri Lhokseumawe, 2024)
Augmented reality (AR) is a technology that combines two- dimensional or three-dimensional virtual objects into the real world that presents in real-time form. The AR implementation in this study will be applied to the introduction of historical buildings that are expected to provide information and attract tourism interest that choose Aceh Tamiang as a tourist choice, AR will use markers as a tool to display a 3D building object using a feature from accelerated segment test algorithm (FAST ), the way the FAST method works is to detect natural point values contained in a marker, to get a good tracking result, we need a marker that has many point values, the more point values are in the marker, the faster the tracking process is done. To find out whether the application can work properly then several tests are carried out, from the test results obtained different accuracy values on the results of the test data that is, the marker detection test obtained 100% accuracy value, testing at a distance with an accuracy value of 83%, testing on 50% light intensity, testing on the detection of marker slope 80%, and Application Test Results at 4 Devices is 100%.